(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Zinchenko V. М. Psychopedagogical basis for teaching ukrainian language in philology specialized classes. The article determines psychopedagogical basis for teaching ukrainian language in philology specialized classes. The terms «aptitude», «talent» and views of psychology scholars on the Ukrainian language study were also researched.